2017
DOI: 10.1038/s41598-017-12392-6
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine aminotransferase activity of Aro8/Aro9 engage tryptophan degradation by producing kynurenic acid in Saccharomyces cerevisiae

Abstract: Kynurenic acid (KA) is a tryptophan (Trp) metabolite that is synthesised in a branch of kynurenine (KYN) pathway. KYN aminotransferase (KAT) catalyses deamination of KYN, yielding KA. Although KA synthesis is evolutionarily conserved from bacteria to humans, the cellular benefits of synthesising KA are unclear. In this study, we constructed a KAT-null yeast mutant defective in KA synthesis to clarify the cellular function of KA. Amino acid sequence analysis and LC/MS quantification of KA revealed that Aro8 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 57 publications
2
26
1
Order By: Relevance
“…As compared with similar enzymes, AroH displays an analogous preference for L-tyrosine, L-phenylalanine and α-aminoadipate as amino donors (Karsten et al, 2011 ). We also demonstrated that it is able to metabolize L-kynurenine, as already suggested for Aro8 based on studies on knock-out yeast mutants (Ohashi et al, 2017 ) reporting that the enzyme is responsible for tryptophan catabolism to kynurenic acid. However, it should be pointed out that the K m of L-kynurenine of AroH is 5 to 20-fold higher than that for aromatic substrates.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…As compared with similar enzymes, AroH displays an analogous preference for L-tyrosine, L-phenylalanine and α-aminoadipate as amino donors (Karsten et al, 2011 ). We also demonstrated that it is able to metabolize L-kynurenine, as already suggested for Aro8 based on studies on knock-out yeast mutants (Ohashi et al, 2017 ) reporting that the enzyme is responsible for tryptophan catabolism to kynurenic acid. However, it should be pointed out that the K m of L-kynurenine of AroH is 5 to 20-fold higher than that for aromatic substrates.…”
Section: Resultssupporting
confidence: 82%
“…Yeast Aro8 is a broad specificity dimeric aminotransferase belonging to the Fold Type I family of PLP-enzymes (Bulfer et al, 2013 ), able to metabolize both aromatic amino acids and α-aminoadipate (Iraqui et al, 1998 ). It has been recently claimed as one of the enzymes involved in L-tryptophan degradation (Ohashi et al, 2017 ). A detailed study on the main genes playing a role in A. fumigatus virulence, does not include Aro proteins (Abad et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of KYNA in yeast raises the question about its role in microorganisms. It was suggested that KYNA pathway can be essential for the detoxification of tryptophan excess and remain the way for the transformation of this amino acid to the less toxic KYNA (Ohashi, Chaleckis, Takaine, Wheelock, & Yoshida, 2017). In addition to yeasts, the kynurenine pathway was documented in some prokaryotes such as Streptomyces antibioticus and Xanthomonas pruni (Kurnasov et al, 2003).…”
mentioning
confidence: 99%
“…Kynurenine pathway is crucial in prokaryotic and eukaryotic cells for tryptophan catabolism and synthesis of the important cofactor NAD + (Ohashi et al, 2017). KYNA is formed along the kynurenine pathway via deamination of kynurenine; the enzymatic step is catalysed by kynurenine aminotransferases (KATs).…”
mentioning
confidence: 99%
“…Aro8 is an aromatic aminotransferase involved in aromatic amino acids metabolism (tryptophan, tyrosine, and phenylalanine). Aro8 takes part in the branch of the kynurenine pathway by synthesizing kynurenic acid indirectly from tryptophan (Trp) [29]. Free tryptophan can be metabolized in vivo and play key roles as an antioxidant [30].…”
Section: Discussionmentioning
confidence: 99%